2007
DOI: 10.1002/ar.20574
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Temporary Airway Epithelial Repopulation and Rare Clonal Formation by BM‐derived Cells Following Naphthalene Injury in Mice

Abstract: The goal of the study was to investigate participation of bone marrow (BM) cells in the process of airway epithelial restoration after naphthalene-induced injury. We transplanted sex-mismatched green fluorescent protein (GFP) -tagged BM-derived cultured plastic-adherent mesenchymal stem cells into 5Gy-irradiated C57BL/6 recipients. After 1 month of recovery, experimental animals were subjected to 250 mg/kg naphthalene IP. Animals were killed at 2-30 days after naphthalene. By immunofluorescence, immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…However, in reports that provided evidence of engraftment and differentiation by systemic administration of BM-derived stem cells, the frequency in airways is very low ( < 1%). We and others [11,16] have delivered BM cells directly (by intratracheal instillation) to the lung after lung injury in mice, with results similar to the systemic administration route. Meanwhile, engraftment studies have been made also in CF mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in reports that provided evidence of engraftment and differentiation by systemic administration of BM-derived stem cells, the frequency in airways is very low ( < 1%). We and others [11,16] have delivered BM cells directly (by intratracheal instillation) to the lung after lung injury in mice, with results similar to the systemic administration route. Meanwhile, engraftment studies have been made also in CF mice.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies in mouse models have suggested that bone marrow (BM)-derived hematopoietic stem/progenitor cells (HSPCs) can localize to the lung and acquire phenotypic markers of airway and alveolar epithelium, vascular endothelium, and interstitial cells [7][8][9][10][11]. There is also evidence that blood-borne stem cells may contribute to lung tissue in recipients of BM or lung transplantation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several studies have demonstrated the ability of marrow-derived hematopoietic stem/progenitor cells (HSPCs) to home to the lung and transform into epithelial cells [Krause et al, 2001;Grove et al, 2002;Theise et al, 2002;Abe et al, 2004;Serikov et al, 2007]. There is also evidence that bloodborne stem cells may contribute to lung tissue in recipients of bone marrow or lung transplantation [Kleeberger et al, 2003;Suratt et al, 2003;Mattsson et al, 2004].…”
Section: Acquisition Of Lung Cell Phenotype By Marrowderived Stem Celmentioning
confidence: 99%
“…Previously, staining for Y chromosome [12] or for both Y and X chromosomes [28] was effectively used to determine the possibility of cell fusion. In this study we did not perform this analysis because we previously had shown that GFP is a reliable tag of engrafted cells by Y chromosome staining in sex-mismatched transplantations [23]; therefore, we checked only GFP-positive cells for polyploidy, which was not observed. Because we were not able to demonstrate physiologically important or long-term engraftment of bone marrow cells as specialized epithelial or endothelial cells, analysis of the possibility of cell fusion was not warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In 5-Gy-irradiated chimeric mouse subjected to naphthalene-induced lung injury, we found very limited engraftment of bone marrow-derived mesenchymal stem cells in the bronchial epithelium [23], although in vitro these cells were capable of endodermal differentiation [24]. Homing of BMDC to the lung and their possible differentiation into specialized cells of endothelial or epithelial lining, as well as participation in postinflammatory lung fibrosis following acute bacterial pneumonia, have not yet been studied.…”
Section: Introductionmentioning
confidence: 86%